Religious Perspectives on Ecological, Political, and Cultural Grief: What Role Is Played by Structural Grief? - Michael S. Hogue (Religions, 2025)
We live in a time of the world’s unmaking: species extinction, climate emergency, democratic deconsolidation, rising authoritarianism, economic instability, pandemics, political polarization, cyberwarfare, geopolitical realignments [...]